India's Public Education Subsidies (International Journal of Innovative Research in Engineering & Management, 2023)
The purpose of this paper is to examine how  higher education in India is currently supported, as well as  the viability as well as feasibility of alternative financing  plans. In India, the government pays for the majority of  higher education. Furthermore, since higher education  helps both individuals and communities, and since it draws  society's wealthier members, a case might be made for  moving the economic strain from the social to the private  realm. Given financial constraints and concerns about  justice, it is suggested that paying higher education largely  via general tax revenue may not be the best long-term plan.  As a consequence, many policy solutions are considered,  including public support of higher education, student  loans, graduate tax, student fees, and private sector  engagement. A discriminating pricing system, it is said,  would be the most efficient and equitable of the  possibilities. While the government will continue to fund a  large portion of higher education costs owing to  socioeconomic and political realities, efforts should be  made to build a funding model that integrates a range of  techniques rather than relying on a single one. Fee and  subsidy policies should also be differentiated across  several levels as well as varieties of higher education,  according to the authors.
Keywords: Education Subsidies; Efficient Education; Fair Education